(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Broad ligament pregnancy is a rare obstetric condition. Its diagnosis is quite difficult andmanagement is challenging. Here we report a case of a 26 years old primi gravida conceivedfollowing laparoscopy and ovulation induction. Diagnosis of the broad ligament pregnancywas done by a transvaginal ultrasound at her 9 weeks and was proceded with laparoscopyfollowed by laparotomy. A right broad ligament pregnancy was found and the sac with fetuswas removed. Laparoscopy was converted into a laparotomy as there was an uncontrollablebleeding from the broad ligament. Here we present a case of this extreme rare type of broadligament pregnancy. Bangladesh J Obstet Gynaecol, 2018; Vol. 33(2) : 164-166